Участь православного духовенства Волинської губернії в діяльності «Союза русского народа» - Боярчук, Андрій; Boyarchuck, Andrei (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розкрито участь православного духовенства Волинської губернії в діяльності чорносотенної організації «Союза русского народа». Показано структурну організацію Почаївського відділу СРН, визначено частку пред¬ставників духовенства, що були окружними старостами й організаторами його низових ланок. Охарактеризовано діяльність волинських кліриків-чорносотенців в економічній, громадській та культурно-просвітницькій сферах. The article reveals the participation of the Orthodox clergy of the Volyn province in the activities of the organization «Union of the Russian people». The structural organization of the Pochayiv Department of the SRN is shown, and a certain proportion of the clergy, who were district chiefs and organizers of its grass roots, were determined. This is a description of the activities of Volyn clerics in the economic, social and cultural-educational spheres.
Participation of the Orthodox Clergy of the Volyn Province in the Activities of the «Union of the Russian People»
Keywords: «Союз русского народа»; чорносотенці; Почаївський відділ СРН; союзний староста; священик; «Union of the Russian people»; the Pochayiv branch of the SRN; the Union chief of staff; the priest